Welcome, new brand colleague! A conceptual framework for efficient and effective human–AI co-creation for creative brand voice - Alexandra Kirkby; Carsten Baumgarth; Jörg Henseler (Journal of Brand Management, 2025)
The rapid advancement of artificial intelligence (AI) capabilities has extended into creative realms, presenting opportunities for creative collaboration between human brand professionals and AI in support of brand voice efforts. However, there remains little clarity regarding the implementation of this creative interaction. With a conceptual approach, the current research proposes a three-level framework of human–AI co-creation for creative brand voice that highlights key factors that can facilitate brand efficiency and effectiveness at the individual (AI task roles, co-creation teaming, knowledge and skills), organisational (infrastructure and brand voice database, socialisation), and societal (responsibility and accountability, AI transparency, brand voice copyright) levels. Each level presents different challenges and insights. At the individual level, it is critical to consider operational processes; at the organisational level, managing the interactions is key; and at the societal level, external influences must be accounted for, to manage the brand. This research contribution in turn offers theoretical guidance, aligned with a high-level brand management perspective, on how to pursue efficiency and effectiveness at three defined levels, as well as relevant avenues for further research.
Keywords: 330; Brand management; Artificial intelligence; Brand voice; Co-creation; Creativity